Konsep dan peran manajemen resiko dalam mewujudkan good corporate governance pada perbankan syariah di Indonesia - Khatimah, Khusnul (Maliki Interdisciplinary Journal, 2024)
Businesses, including Islamic banking, always face risks. The aim of this study is to understand how the concept and role of risk management contribute to achieving good corporate governance in Islamic banking. This research employs a literature review method to address the research questions. The findings indicate that risk management plays a crucial role in achieving good corporate governance in Islamic banking.